Analytical modelling of the effect of squeeze film damping on the frequency and quality factor of a poly MUMPs resonator - Algamili, A. (Institute of Advanced Scientific Research, Inc., 2020)
This paper reports analytical modelling of the squeeze film damping effect of a standard Polysilicon Multi-Users MEMS Process (Poly MUMPs) resonators. Poly MUMPs resonator has been designed for the purpose of gas detection. Generally, damping is present in all vibrating systems in the real world with an exception of systems vibrating in a vacuum environment. The air damping is considered the major source of energy dissipation and has a main influence on these vibration systems. To reduce the effect of the squeeze film damping, the movable top plate of the Poly MUMPs resonator has been investigated by changing the size of the etched holes perforated to improve the resonance frequency and quality factor of the Poly MUMPs resonator. Electro thermal actuation method will be used to drive the resonator in the dynamic mode and the output voltage will be measured using an MS3110 universal capacitive readout circuit. The results show that by increasing the size of the etched holes from 6 µm to 10 µm, the squeeze film damping is decreased from 47.303 μN.m to 24.007 μN.m, respectively. This will affect the resonance frequency to increase from 3904.022 Hz to 4483.783 Hz, as well as and the quality factor from 0.999 to 1.912, respectively. © 2020, Institute of Advanced Scientific Research, Inc. All rights reserved.